FOSTERING AUTONOMOUS LEARNING IN EFL: A KEY TO MOTIVATING STUDENTS - Usein, Arafat (International Scientific Journal Vision, 2020)
This paper aims to introduce the concept of student autonomy in the foreign language learning and teaching. The whole picture here is presented to provide a deeper understanding of the concept of autonomous learning. Learner autonomy is an important concept in educational fields. This section will consider what learner autonomy is, what skills autonomous learners need and why learner autonomy is important. The paper also looks at how learner autonomy can be developed, as well as considering the cultural aspects of learner autonomy. This article examines whether the English Language Preparatory School students at the International Balkan University are prepared to be engaged in autonomous language learning. The questionnaire used in the research are administered to 34 students. Students’ responses are rated on five points for each item as: 1.Strongly Agree, 2.Agree, 3.Unsure, 4.Strongly Disagree, and 5.Disagree. According to the results of the questionnaires, the students show their attitudes towards the autonomous learning. Some pedagogical implications for fostering student autonomy will be recommended and also some suggestions for further researches will be offered.